Entre la distopía y la heterotopía: espacios de la crisis en las novelas de Isaac Rosa - Łukasz Smuga (Studia Romanica Posnaniensia, 2022)
This paper analyses urban spaces of crisis in Isaac Rosa’s novels La mano invisible (2011), La habitación oscura (2013), and the graphic novel Aquí vivió. Historia de un desahucio (2016) by Cristina Bueno and Isaac Rosa. It explores the dystopian and realistic elements in Rosa’s fiction and proposes to read his works through the lens of Michel Foucault’s essay on other spaces. The article argues that the unusual, quasi-dystopian spaces are of a double nature, typical for heterotopias, and play a significant role in the manner in which Rosa depicts the consequences of the economic crisis in Spain at the beginning of the 21st century.